Attention and its crisis in digital society - Campo, Enrico (Oxon: Routledge, 2022)
"In the context of debates surrounding the effects of new technologies on our mental faculties, particularly the attention span, this volume addresses the notion of a deterioration of attention, and the related ideas of cognitive overload, an inability to concentrate, and attention deficit disorder. Through a new conceptualisation of attention based not on individualistic or universalistic approaches, but centred instead on the cultural and social variability of cognitive processes and the multiplicity of forces and environments that encourage, stimulate and inhibit certain cognitive mechanisms, the author rejects the idea of a degradation or crisis of attention and proposes an alternative vision of the problem of attention in contemporary societies. Placing cultural conventions, social norms and ecological environments at the forefront of our understanding of individual and collective attention, Attention and its Crisis in Digital Society will appeal to scholars of sociology, psychology and philosophy with interests in social theory, cognitive processes and the criticisms often levelled at digital society and new technologies"--
Includes bibliographical references and index.
Keywords: Distraction (Psychology); Attention; Information society; Information technology -- Social aspects